In situ observation of the magnetocaloric effect through neutron diffraction in the Tb(DCO2)3 and TbODCO3 frameworks. Issue 35 (19th August 2020) - Dixey, Richard J. C.; Manuel, Pascal; Orlandi, Fabio; Mukherjee, Paromita; Dutton, Siân E.; Stenning, Gavin B. G.; Saines, Paul J.
Abstract : Understanding large entropy changes in efficient magnetocaloric materials is essential to design next-generation magnetocaloric devices. We report the large entropy change mechanism in two efficient magnetocaloric materials – TbODCO3 and Tb(DCO2 )3 . Abstract : Probing the magnetic structure of magnetocaloric materials in applied fields, can reveal detailed insight into the mechanism of magnetic refrigeration thereby linking the magnetic states that form under applied magnetic fields to changes in magnetic entropy. This study probes the long range magnetic order in Tb(DCO2 )3 and TbODCO3 as a function of temperature and applied magnetic field, through neutron diffraction measurements. A triangular Ising antiferromagnetic phase is formed, in small applied magnetic fields in Tb(DCO2 )3, a spin flip transition occurs to a simple ferromagnetic structure in higher applied fields. TbODCO3 undergoes a phase transition, in applied fields, into two magnetic phases; namely a buckled chain ferromagnetic phase along the b -axis and a canted antiferromagnetic phase, with a ferromagnetic component along c -axis. Both of the states observed in TbODCO3 are consistent with Ising-like anisotropy previously reported in TbODCO3 and the coexistance of these is likely the result of applying a magnetic field to a powdered sample.